2021
DOI: 10.1007/s13202-021-01361-5
|View full text |Cite
|
Sign up to set email alerts
|

A review on low salinity waterflooding in carbonates: challenges and future perspective

Abstract: Low salinity waterflooding has gained significant attention and importance in the last decade, as it is seen as an impactful method for recovery of additional oil from carbonate reservoirs. Existing literature does not do justice to the underlying mechanisms that aid in the recovery of additional oil from such rock types. In this paper, we present a comprehensive review of the research conducted on low salinity waterflooding in carbonates and further provide a detailed and critical analysis on the same. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…One of the main reasons behind these inconsistencies can be related to the absence of consensus on the optimum composition of the brine to be injected. This can be explained by the fact that the mechanism of CSW is not fully understood [8][9][10][11][12][13]. It is widely accepted that additional recovery is primarily accompanied by wettability alteration to a less oil-wet state [14].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main reasons behind these inconsistencies can be related to the absence of consensus on the optimum composition of the brine to be injected. This can be explained by the fact that the mechanism of CSW is not fully understood [8][9][10][11][12][13]. It is widely accepted that additional recovery is primarily accompanied by wettability alteration to a less oil-wet state [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mineral dissolution is not considered the main mechanism that alone results in increased oil recovery through LSW injection. [ 21,28,30 ]…”
Section: Lsw Floodingmentioning
confidence: 99%
“…The primary PDIs for LSW flooding in carbonate surfaces are SO 4 2− , Ca 2+ , and Mg 2+ , which tend to impact oil recovery depending on their concentration and temperature positively. [ 21 ]…”
Section: Lsw Floodingmentioning
confidence: 99%
“…LSE mechanisms could be classified into two types: fluid–fluid interactions and solid–fluid interactions. Solid–fluid interactions include pH increase, MIE, EDL expansion, fines migration, salt in effect, and mineral dissolution, and fluid–fluid interactions include osmotic effect, formation of microdispersion, increased O/W interfacial viscoelasticity or snap-off effects, and fluid coalescence. Many reports of the underlying mechanisms in the literatures are related to rock–fluid interactions. Little attention is paid to fluid–fluid interactions as a key mechanism for LSE .…”
Section: Proposed Lse Mechanismsmentioning
confidence: 99%
“… , In the recent 5 years, more and more attentions have been focused on the potential EOR/IOR of LSW in petroleum, and hence, review publications increased (Table ). With deeper exploration, microdispersion formation, snap-off, fluid coalescence, and more were suggested as promising LSE mechanisms. Tetteh et al concluded that microdispersion formation would be one of the future directions for LSW . Wettability alteration is considered as the main reason for LSE in sandstone and carbonate, which was explained both by DLVO and non-DLVO theories .…”
Section: Introductionmentioning
confidence: 99%